Novel amphiphilic cationic porphyrin and its Ag(II) complex as potential anticancer agents - Tovmasyan, Artak; Babayan, Nelli; Poghosyan, David; Margaryan, Kristine; Harutyunyan, Boris; Grigoryan, Rusanna; Sarkisyan, Natalia; Spasojevic, Ivan; Mamyan, Suren; Sahakyan, Lida; Aroutiounian, Rouben; Ghazaryan, Robert; et al. (Journal of inorganic biochemistry, 2014)
In the present study we have synthesized a novel amphiphilic porphyrin and its Ag(II) complex through modification of water-soluble porphyrinic structure in order to increase its lipophilicity and in turn pharmacological potency. New cationic non-symmetrical meso-substituted porphyrins were characterized by UV–visible, electrospray ionization mass spectrometry (ESI-MS), 1H NMR techniques, lipophilicity (thin-layer chromatographic retention factor, Rf), and elemental analysis. The key toxicological profile (i.e. cytotoxicity and cell line- (cancer type-) specificity; genotoxicity; cell cycle effects) of amphiphilic Ag porphyrin was studied in human normal and cancer cell lines of various tissue origins and compared with its water-soluble analog. Structural modification of the molecule from water-soluble to amphiphilic resulted in a certain increase in the cytotoxicity and a decrease in cell line-specificity. Importantly, Ag(II) porphyrin showed less toxicity to normal cells and greater toxicity to their cancerous counterparts as compared to cisplatin. The amphiphilic complex was also not genotoxic and demonstrated a slight cytostatic effect via the cell cycle delay due to the prolongation of S-phase. As expected, the performed structural modification affected also the photocytotoxic activity of metal-free amphiphilic porphyrin. The ligand tested on cancer cell line revealed a dramatic (more than 70-fold) amplification of its phototoxic activity as compared to its water-soluble tetracationic metal-free analog. The compound combines low dark cytotoxicity with 5 fold stronger phototoxicity relative to Chlorin e6 and could be considered as a potential photosensitizer for further development in photodynamic therapy. The cytotoxicity of amphiphilic Ag(II) porphyrin on various cancer and normal cells is presented and compared to that of cisplatin. [Display omitted]